2018
DOI: 10.1111/liv.13726
|View full text |Cite
|
Sign up to set email alerts
|

Detecting liver injury non‐invasively using hyperpolarized 13C MRI

Abstract: See Article on Page 1117

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In vivo visualization of GSH-mediated biotransformation offers a promising method for in-depth investigations of these processes in liver that may have not been well studied before. Due to the aforementioned reasons, in vivo real-time visualization techniques for GSH-mediated biotransformation are in great demand in both biomedical research and clinical practice. Recently, several fluorescence-based imaging methods have been developed, including a fluorescent imaging technique based on thiol-activatable gold nanoprobes, which accomplished in vivo monitoring of GSH-mediated biotransformation at the molecular level and indicated that this process can be used to modulate the in vivo transport of nanoparticles. , However, the shortcomings of current fluorescence imaging, such as restricted penetration depth, significant autofluorescence interference, and limited anatomical information, impose substantial difficulties for further popularization of these fluorescence-based imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo visualization of GSH-mediated biotransformation offers a promising method for in-depth investigations of these processes in liver that may have not been well studied before. Due to the aforementioned reasons, in vivo real-time visualization techniques for GSH-mediated biotransformation are in great demand in both biomedical research and clinical practice. Recently, several fluorescence-based imaging methods have been developed, including a fluorescent imaging technique based on thiol-activatable gold nanoprobes, which accomplished in vivo monitoring of GSH-mediated biotransformation at the molecular level and indicated that this process can be used to modulate the in vivo transport of nanoparticles. , However, the shortcomings of current fluorescence imaging, such as restricted penetration depth, significant autofluorescence interference, and limited anatomical information, impose substantial difficulties for further popularization of these fluorescence-based imaging techniques.…”
Section: Introductionmentioning
confidence: 99%